Determinan Positif Emotion dan Implikasinya terhadap Impulse Buying pada Pelanggan H&M - Sephiani, Mutiara; Humairoh (BUDGETING : Journal of Business, Management and Accounting, 2025)
Today, consumers buy products based on necessity and are influenced by their lifestyle and involvement in fashion. This phenomenon is further reinforced by advances in information technology and social media. This research uses quantitative methods; the research population of 1,082,728 people was minimized using the Slovin formula, which resulted in 99.9 rounded up to 100 respondents. The analysis method uses path analysis and the sobel test. The results of the coefficient of determination test obtained from the Adjusted R-Square value of 0.947 or 94.7% indicate that the variables of shopping lifestyle, fashion involvement, and positive emotion contribute jointly to the impulse buying variable, and the remaining 5.3% are influenced by other variables. The results of the positive emotion research were able to mediate the influence of the shopping lifestyle and fashion involvement variables on impulse buying. The novelty of this study from previous research is that no previous research jointly examines the relationship between shopping lifestyle and fashion involvement in impulse buying, which uses positive emotion as an intervening variable. This research is expected to provide deeper insight into consumer behavior in the fashion retail sector.   Keywords: Fashion Involvement, Impulse Buying, Positif Emotion, Shopping Lifestyle